PENGARUH TOTAL HUTANG DAN MODAL KERJA TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DIBURSA EFEK INDONESIA Periode (2017-2020) - Mei Hotma Mariati; Kristina Sinaga (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2021)
ABSTRACT This study aims to determine and analyze the effect of Total Debt and Working Capital on Net Profit, either partially or simultaneously in the Consumer Goods Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The population in this study is the Consumer Goods Industrial Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2020 period, totaling 52 companies. The sample selection used purposive sampling technique. The number of samples obtained as many as 31 companies. Data obtained through www.idx.co.id. The analytical method used is multiple linear regression analysis with the SPSS 22 application. The results show that Total Debt and Working Capital simultaneously have a significant effect on the Net Profit of Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange for the 2017-2020 period. Total Debt and Working Capital partially have a positive and significant effect on the Net Profit of Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange for the 2017-2020 period.